Utilization of Kersen Leaves as Antihyperuricemia - Nita Parisa; Aprilia Paskah Samosir; Fatmawati Fatmawati; Rachmat Hidayat; Marlyani Tamara; Karina Nurul Fahira; Alfiyah Munawwaroh Abdullah; Rischka Salsabila Maulini; Rohaya Rohaya (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Kersen (Muntingia calabura), a tropical plant originating from Latin America, is a wild plant that has many benefits. Kersen contains flavonoid compounds, tannins, triterpenes, saponins, alkaloids that are useful as anti-inflammatory, anti-tumor, and anti-uric acid. Hyperuricemia is a metabolic disease characterized by high levels of uric acid in the blood which precipitates uric acid crystals in the kidneys and joints. Most patients with hyperuricemia do not require medical therapy, but lifestyle modifications can be made such as regular eating, adequate exercise, and avoiding foods and drinks high in protein and purines. This study aims to investigate the benefits of Kersen Leaf as an anti-uric acid. The method used in this study is a literature study based on library sources excavated through national and international sites such as Google, Google Scholar, and PubMed.